Exploring The Transatlantic Divide: American Vs British Slang In 'Wild Child' Movie - Maharani, Laura Meylinda; Karani, Elanneri; Haryani, Tutik; Tegar, Jonathan; Mieyrandha (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This "Transatlantic Divide" between AmE and BrE refers to one of the most prominent sociolinguistic phenomena, especially in slang usage. To date, prior research into slang has commonly been restricted to studying single regional varieties or comparing lists without considering their narrative and sociocultural functions. This paper, therefore, aims to bridge this gap by discussing the sociolinguistic function of the interplay between AmE and BrE slang in the 2008 teen comedy film Wild Child. The research applies a descriptive qualitative method with a content analysis approach to analyze the dialogue in the movie in order to find, categorize, and interpret slang expressions according to their communicative and narrative roles. These results show two different sociolinguistic functions. First, local varieties of AmE and BrE slang serve as linguistic barriers, creating conflict, misunderstanding, and marking social distance between characters. The differences underline the construction of "in-group" and "out-group" identities and focus on cultural dissonance. Second, a category of mutually intelligible expressions or "global slang" serves as a linguistic bridge that fosters mutual understanding, emotional connection, and integration of the characters. In these ways, the movie presents language both as a source of division and as a means of reconciliation. The paper concludes that Wild Child effectively mobilizes the Transatlantic Divide not merely from a stylistic or comedic perspective but as a core narrative mechanism. Slang is used as a means through which social hierarchies, cultural adaptation, and identity negotiation are dramatized, showing how linguistic variation drives both conflict and harmony in cross-cultural communication.